Effect of Some Plants Extracts on the Viability of Protoscoleces in Vitro - Tuhfa T. Al-Aloosi; A. A. Al-Tai; A. M. Al-Samarrai (Tikrit Journal of Pure Science)
This study was conducted to evaluate the protoscolicidal effect of four plants alcoholic extracts on protoscoleces of the parasite Echinococcus granulosus in vitro. The plants that had been used in this study were: Viscum album (Mistletoe) and Prunus armeniaca (Apricot bitter kernels) with concentrations of 375, 750 and 1500 mg/ml, also Syzygium aromaticum (Clove flower buds) and Capsicum frutescence (Chili pepper) with concentrations of 375, 750 and 1500 µg/ml. All extracts were treated at four periods (15, 30, 45 and 60 min.).